Influence of Entrepreneurial Literacy and Social Capital on Entrepreneurial Intentions with Attitude as a Moderating Variable among Economic Education Students at Jambi University - Ezer Sinaga, Frin Eben; Muazza; Suratno; Mayasari (LP2M IAIN Palopo, 2025)
This study examines the influence of entrepreneurial literacy and social capital onentrepreneurial intentions, with attitude serving as a moderating variable, amongEconomic Education students at Jambi University. The primary objective is toidentify how knowledge, social networks, and psychological disposition interact toshape students’ entrepreneurial aspirations. A quantitative research design wasapplied, utilizing a survey method with a sample of 121 students from the2021–2022 cohort. Path analysis was employed to test the relationships amongvariables and to evaluate the moderating role of attitude.The results demonstrate that entrepreneurial literacy has a significant positiveef ect on entrepreneurial intentions, indicating that students with higherentrepreneurial knowledge and skills are more likely to engage in entrepreneurialactivities. Similarly, social capital was found to positively influenceentrepreneurial intentions, emphasizing the role of networks, trust, and socialsupport in fostering entrepreneurship. Moreover, attitude significantly moderatesthese relationships, strengthening the impact of both entrepreneurial literacy andsocial capital on entrepreneurial intentions.These findings highlight the importance of integrating entrepreneurship literacyand social networking opportunities within higher education curricula whilefostering positive entrepreneurial attitudes. Future research is recommended toexpand the model across dif erent institutions and employ longitudinal designs toexamine causal relationships more comprehensively.